Bulky iminophosphine‐based nickel and palladium catalysts bearing 2, 6‐dibenzhydryl groups for ethylene oligo‐/polymerization. (6th January 2020) - Wu, Qitong; Wang, Wenbing; Xu, Guoyong; Pang, Wenmin; Li, Yougui; Tan, Chen; Wang, Fuzhou
Abstract : A series of 2, 6‐dibenzhydryl substituted bulky Ni and Pd complexes containing P, N‐chelating ligands, {[2, 6‐(Ph2 CH)2 ‐4‐R‐C6 H2 ‐N=CH‐C6 H4 ‐2‐PPh2 ]MX2 ; MX2 =NiBr2 ; R = Me (Ni1 ); R = F (Ni2 ); MX2 =PdCl2, R = Me (Pd1 )}, have been prepared and used as catalyst precursors for ethylene oligo‐/polymerization. Compared to the corresponding 2, 6‐diisopropyl Ni catalyst, these bulky Ni precatalysts activated by Et2 AlCl exhibited excellent catalytic performance toward ethylene polymerization with activity of up to 1.90 × 10 5 g PE (mol Ni) −1 h −1, and result in semicrystalline PEs with high molecular weight. The catalytic performance of these bulky P, N‐type complexes was significantly improved by introducing two ortho‐ dibenzhydryl on the N‐aryl substituents. However, the formation of C10 –C24 oligomers were generated using their palladium catalysts through ethylene oligomerization at high temperatures. Abstract : Bulky 2, 6‐dibenzhydryl‐based P, N‐type Ni and Pd catalyzed ethylene oligo ‐/polymerization. Ni catalysts generated high molecular weight semicrystalline PEs, but their Pd conducted ethylene oligomerization to give C10 ‐C24 oligomers at high temperature.